Preparation method of fossil-based hard carbon material

A method for preparing fossil-based hard carbon materials using recycled bamboo chopsticks and wheat flour addresses surface detachment issues, enhancing conductivity and adhesion, thereby improving battery performance and environmental sustainability.

CN119191277AActive Publication Date: 2024-12-27SHAANXI PUSTAR ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411740118.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2024-12-27
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Existing methods for preparing hard carbon materials face issues with surface detachment during high-temperature treatments, leading to structural damage and performance degradation in battery applications.

Method used

A method involving preliminary carbonization, additive preparation, cross-linking with carbohydrates, and controlled heating processes to produce a fossil-based hard carbon material, utilizing recycled bamboo chopsticks and wheat flour to enhance adhesion and conductivity.

Benefits of technology

The method improves the adhesion and conductivity of the hard carbon material, resulting in better battery performance and reduced environmental impact through resource recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a fossil-based hard carbon material, and relates to the technical field of hard carbon materials, and the preparation method comprises the following steps: S1, selecting a fossil-based raw material, carrying out preliminary carbonization treatment on the raw material, and grinding and sieving to obtain a preliminary carbonized material; s2, preparing a first additive for later use; and S3, preparing a second additive for later use. The wheat flour and the copper deposition liquid are mixed to obtain the second additive, the second additive is added into the modified additive to be mixed with the primary carbonized material to obtain the hard carbon material, the wheat is ground and then mixed with the copper deposition liquid, and therefore the wheat flour has electrical conductivity; after the natural polyphenols are mixed and reacted with the first additive, a polymer is formed by cross-linking and is grafted to the surface of the primary carbonized material, so that a large number of conductive substances exist on the surface of the primary carbonized material, electroless deposition of copper metal is realized, and the performance of a battery made of the hard carbon material is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hard carbon materials, and in particular to a method for preparing a fossil-based hard carbon material. Background Art

[0002] Hard carbon material is a carbon material prepared by specific physical and chemical treatment methods using fossil base as the main raw material. Hard carbon is widely used in battery negative electrode materials due to its high rate, low temperature resistance and long cycle characteristics.

[0003] In the prior art, during the preparation of hard carbon materials, the raw materials need to be subjected to multiple high-temperature treatments. During the high-temperature treatments, the surface base of the raw materials is easily detached, thereby destroying the overall structure of the hard carbon and affecting the performance of batteries made of the hard carbon materials. Based on this, the present invention provides a method for preparing a fossil-based hard carbon material.

[0004] Therefore, we proposed a method for preparing fossil-based hard carbon materials in order to solve the above problems. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a fossil-based hard carbon material. The battery made of the hard carbon material prepared by the present invention has good performance.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a fossil-based hard carbon material, comprising the following steps: S1: Select fossil-based raw materials, perform preliminary carbonization treatment on the raw materials, and obtain preliminary carbonized materials after grinding and sieving; S2: preparing the first additive for standby use; S3: preparing the second additive for standby use; S4: mixing the first additive obtained in step S2 with the second additive obtained in step S3 to obtain a modified additive; S5: mixing the preliminary carbonized material obtained in step S1 with the modified additive obtained in step S4 to obtain a precursor; S6: cross-linking the precursor obtained in step S5 with carbohydrates, obtaining an intermediate after sintering and annealing, and preparing a fossil-based hard carbon material by curing and carbonizing the intermediate. The carbohydrate in step S6 is corn starch.

[0007] Furthermore, the fossil-based raw material is selected from any one of anthracite, bituminous coal and lignite.

[0008] Furthermore, the first additive is prepared by the following method: recycled bamboo chopsticks are selected as raw materials, and the preparation operation is started after the recycled bamboo chopsticks are washed and dried, and the recycled bamboo chopsticks are sent to a grinder for processing for 4 to 6 minutes to obtain bamboo chips, and the bamboo chips are mixed with potassium hydroxide solution and added into a beaker, wherein the mass ratio of the bamboo chips to the potassium hydroxide solution is 1:3, and the mixture is heated to 80 to 90°C, and the mixture is kept warm for reaction for 4 to 6 hours. After the reaction is completed, the mixture is cooled to room temperature, and deionized water accounting for 50 to 60% of the mass of the potassium hydroxide solution is added, and the mixture is evenly mixed and filtered to obtain slurry, and the slurry is sent into an oven, and the temperature is set to 85 to 95°C for 50 to 60 minutes to obtain bamboo fiber.

[0009] Furthermore, bamboo fiber mixed with tris(hydroxymethyl)aminomethane) solution is added into a beaker, wherein the mass ratio of bamboo fiber to tris(hydroxymethyl)aminomethane is 1:0.5, and the mixture is reacted at room temperature for 5 to 10 minutes, with continuous stirring during the reaction. After the reaction, the mixture is put into an oven and set at 80 to 90° C. for 2 to 3 hours to obtain the first additive.

[0010] Furthermore, the second additive is prepared by the following method: wheat grains are selected as raw materials, and wheat flour is obtained after the wheat grains are ground and sifted, and the wheat flour is placed in a copper precipitation solution, and the mass ratio of the wheat flour to the copper precipitation solution is 1: (1.2-1.4). After the mixing reaction lasts for 10-20 minutes, the wheat flour is filtered to separate the copper precipitation solution, and the flour is spread out in a ventilated place to dry, so as to obtain the second additive.

[0011] Furthermore, the modified additive is prepared by the following method: the first additive and the second additive are fed into a mixer for mixing, the mass ratio of the first additive to the second additive is 1: (1.6-1.8), the mixer is set to stir at medium-low speed for 5-8 minutes, and polydimethylsiloxane accounting for 10-15% of the mass of the first additive is added during the mixing process. After mixing, it is placed in an oven at 60-70°C for 2-3 hours, and then taken out and ground and sieved to obtain the modified additive.

[0012] Furthermore, the screening particle size of the modified additive is ≤65 μm, and the screening particle size of the preliminary carbonized material is ≤80 μm.

[0013] Furthermore, the cross-linking reaction temperature of the precursor and carbohydrate is 250-350°C, the reaction time is 5-12h, and the sintering annealing temperature is 400-500°C.

[0014] Furthermore, the temperature of the curing treatment is 800-1100°C, the heating rate is 20-30°C / min, and the insulation time is 1-2h; the temperature of the carbonization treatment is 1300-1600°C, the heating rate is 8-12°C / min, and the insulation time is 3-6h.

[0015] Furthermore, a fossil-based hard carbon material is prepared by the method for preparing a fossil-based hard carbon material.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention obtains a second additive by mixing wheat flour with a copper precipitation liquid, and after adding the modified additive to mix with a preliminary carbonized material to obtain a hard carbon material, the wheat flour is ground and mixed with the copper precipitation liquid to make the wheat flour conductive. At the same time, natural polyphenols in wheat are used. After the natural polyphenols are mixed with the first additive, they are cross-linked to form a polymer grafted to the surface of the preliminary carbonized material, so that a large amount of conductive substances exist on the surface of the preliminary carbonized material, and the electroless deposition of copper metal is achieved, which effectively improves the performance of the battery made of the hard carbon material; 2. The present invention uses recycled bamboo chopsticks to process the first additive. After being cleaned, crushed, and other treatments, the recycled bamboo chopsticks can collect bamboo fiber materials to cover the surface of the preliminary carbonized material for preparation reaction. The good flexibility and durability of the bamboo fiber prevent the surface base of the preliminary carbonized material from falling off during the preparation process, thereby improving the adhesion performance of the modified additive and thus improving the conductivity of the hard carbon material. 3. The present invention recycles bamboo chopsticks and wheat as the main raw materials for modified additives. The raw materials used are easy to obtain, and the recycled bamboo chopsticks are garbage for secondary use, which can improve resource utilization and reduce environmental pollution caused by garbage. Moreover, the decomposition products are all natural substances with good biodegradability, which can improve the pollution to the environment caused by discarded batteries. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] The present invention obtains a second additive by mixing wheat flour with a copper precipitation liquid, and after adding the modified additive into the modified additive and mixing it with the preliminary carbonized material to obtain a hard carbon material, the wheat flour is ground and mixed with the copper precipitation liquid to make the wheat flour conductive. At the same time, natural polyphenols in wheat are used. After the natural polyphenols are mixed with the first additive and reacted, they are grafted to the surface of the preliminary carbonized material by cross-linking to form a polymer, so that a large amount of conductive substances exist on the surface of the preliminary carbonized material, and the electroless deposition of copper metal is realized, which effectively improves the performance of the battery made of the hard carbon material. The present invention uses recycled bamboo chopsticks to process and prepare the first additive. After the recycled bamboo chopsticks are cleaned, crushed, and other treatments, bamboo fiber materials can be collected and covered on the surface of the preliminary carbonized material for preparation reaction. The good flexibility and durability of the bamboo fiber are used to prevent the surface base of the preliminary carbonized material from falling off during the preparation process, thereby improving the adhesion performance of the modified additive and thus improving the conductivity of the hard carbon material. The present invention uses recycled bamboo chopsticks and wheat as the main raw materials for the modified additive. The raw materials used are relatively easy to obtain, and the recycled bamboo chopsticks are garbage for secondary use, which can improve the utilization rate of resources and reduce environmental pollution caused by garbage. Moreover, the decomposition products are all natural substances with good biodegradability, which can improve the pollution to the environment caused by discarded batteries.

[0019] The raw materials used in the present invention are all commercially available raw materials.

[0020] Embodiment 1

[0021] A method for preparing a fossil-based hard carbon material comprises the following steps: S1. Select fossil-based raw materials, perform preliminary carbonization treatment on the raw materials, and obtain preliminary carbonized materials after grinding and sieving; Among them, anthracite is used as the fossil-based raw material; S2, prepare the first additive for standby use; The first additive is prepared by the following method: selecting recycled bamboo chopsticks as raw materials, washing and drying the recycled bamboo chopsticks before starting the preparation operation, sending the recycled bamboo chopsticks into a grinder for 4 minutes to obtain bamboo chips, mixing the bamboo chips with potassium hydroxide solution and adding them into a beaker, the mass ratio of bamboo chips to potassium hydroxide solution is 1:3, heating to 80°C after mixing, keeping the temperature for 4 hours, cooling to room temperature after the reaction is completed, adding deionized water accounting for 50% of the mass of the potassium hydroxide solution, mixing evenly and filtering to obtain slurry, sending the slurry into an oven, setting 85°C for 50 minutes, and obtaining bamboo fiber; Add bamboo fiber mixed with tris(hydroxymethyl)aminomethane solution into a beaker, the mass ratio of bamboo fiber to tris(hydroxymethyl)aminomethane is 1:0.5, react at room temperature for 5 minutes, stir continuously during the reaction, and put into an oven after the reaction is completed, set at 80°C for 2 hours, to obtain the first additive; S3, prepare the second additive for standby use; The second additive is prepared by the following method: wheat grains are selected as raw materials, the wheat grains are ground and sieved to obtain wheat flour, the wheat flour is placed in a copper precipitation solution, the mass ratio of wheat flour to copper precipitation solution is 1:1.2, after mixing and reacting for 10 minutes, the wheat flour and the copper precipitation solution are separated by filtering, and the mixture is flattened and placed in a ventilated place to dry, thereby obtaining the second additive; S4, mixing the first additive obtained in step S2 with the second additive obtained in step S3 to obtain a modified additive; The modified additive is prepared by the following method: the first additive and the second additive are fed into a mixer for mixing, the mass ratio of the first additive to the second additive is 1:1.6, the mixer is set to stir at a medium-low speed for 5 minutes, polydimethylsiloxane accounting for 10% of the mass of the first additive is added during the mixing process, and after the mixing is completed, it is placed in an oven at 60° C. for 2 hours, and then taken out, ground and sieved to obtain the modified additive; The screening particle size of modified additives is ≤65μm, and the screening particle size of preliminary carbonized materials is ≤80μm; S5, mixing the preliminary carbonized material obtained in step S1 with the modified additive obtained in step S4 to obtain a precursor; S6, cross-linking the precursor obtained in step S5 with carbohydrates, wherein the carbohydrates are corn starch, and obtaining an intermediate after sintering and annealing, and the intermediate is subjected to curing and carbonization treatment to prepare a fossil-based hard carbon material; The cross-linking reaction temperature of the precursor and carbohydrate is 250°C, the reaction time is 5h, and the sintering annealing temperature is 400°C; The temperature of the curing treatment was 800°C, the heating rate was 20°C / min, and the temperature was kept for 1h. The temperature of the carbonization treatment was 1300°C, the heating rate was 8°C / min, and the temperature was kept for 3h. This embodiment also provides a fossil-based hard carbon material, which is prepared by the method for preparing a fossil-based hard carbon material.

[0022] Embodiment 2

[0023] A method for preparing a fossil-based hard carbon material comprises the following steps: S1. Select fossil-based raw materials, perform preliminary carbonization treatment on the raw materials, and obtain preliminary carbonized materials after grinding and sieving; Among them, bituminous coal is used as the fossil-based raw material; S2, prepare the first additive for standby use; The first additive is prepared by the following method: selecting recycled bamboo chopsticks as raw materials, washing and drying the recycled bamboo chopsticks before starting the preparation operation, sending the recycled bamboo chopsticks into a grinder for 5 minutes to obtain bamboo chips, mixing the bamboo chips with potassium hydroxide solution and adding them into a beaker, the mass ratio of bamboo chips to potassium hydroxide solution is 1:3, heating to 85°C after mixing, keeping the temperature for reaction for 5 hours, cooling to room temperature after the reaction is completed, adding deionized water accounting for 55% of the mass of the potassium hydroxide solution, mixing evenly and filtering to obtain slurry, sending the slurry into an oven, setting 90°C for 55 minutes, and obtaining bamboo fiber; Add bamboo fiber mixed with tris(hydroxymethyl)aminomethane solution into a beaker, the mass ratio of bamboo fiber to tris(hydroxymethyl)aminomethane is 1:0.5, react at room temperature for 7 minutes, stir continuously during the reaction, and put into an oven after the reaction is completed, set at 85°C for 2.5 hours, to obtain the first additive; S3, prepare the second additive for standby use; The second additive is prepared by the following method: wheat grains are selected as raw materials, the wheat grains are ground and sieved to obtain wheat flour, the wheat flour is placed in a copper precipitation solution, the mass ratio of wheat flour to copper precipitation solution is 1:1.3, after mixing and reacting for 15 minutes, the wheat flour and the copper precipitation solution are separated by filtering, and the flour is spread out and placed in a ventilated place to dry, so as to obtain the second additive; S4, mixing the first additive obtained in step S2 with the second additive obtained in step S3 to obtain a modified additive; The modified additive is prepared by the following method: the first additive and the second additive are fed into a mixer for mixing, the mass ratio of the first additive to the second additive is 1:1.7, the mixer is set to stir at a medium-low speed for 6.5 minutes, polydimethylsiloxane accounting for 12% of the mass of the first additive is added during the mixing process, and after the mixing is completed, it is placed in an oven at 65° C. for 2.5 hours, and then taken out, ground and sieved to obtain the modified additive; The screening particle size of modified additives is ≤65μm, and the screening particle size of preliminary carbonized materials is ≤80μm; S5, mixing the preliminary carbonized material obtained in step S1 with the modified additive obtained in step S4 to obtain a precursor; S6, cross-linking the precursor obtained in step S5 with carbohydrates, wherein the carbohydrates are corn starch, and obtaining an intermediate after sintering and annealing, and the intermediate is subjected to curing and carbonization treatment to prepare a fossil-based hard carbon material; The cross-linking reaction temperature of the precursor and carbohydrate was 300°C, the reaction time was 8h, and the sintering annealing temperature was 450°C; The temperature of the curing treatment was 950°C, the heating rate was 25°C / min, and the temperature was kept for 1.5h. The temperature of the carbonization treatment was 1450°C, the heating rate was 10°C / min, and the temperature was kept for 4.5h. This embodiment also provides a fossil-based hard carbon material, which is prepared by the method for preparing a fossil-based hard carbon material.

[0024] Embodiment 3

[0025] A method for preparing a fossil-based hard carbon material comprises the following steps: S1. Select fossil-based raw materials, perform preliminary carbonization treatment on the raw materials, and obtain preliminary carbonized materials after grinding and sieving; Among them, lignite is used as the fossil-based raw material; S2, prepare the first additive for standby use; The first additive is prepared by the following method: selecting recycled bamboo chopsticks as raw materials, washing and drying the recycled bamboo chopsticks before starting the preparation operation, sending the recycled bamboo chopsticks into a grinder for 6 minutes to obtain bamboo chips, mixing the bamboo chips with potassium hydroxide solution and adding them into a beaker, the mass ratio of bamboo chips to potassium hydroxide solution is 1:3, heating to 90°C after mixing, keeping the temperature for reaction for 6 hours, cooling to room temperature after the reaction is completed, adding deionized water accounting for 60% of the mass of the potassium hydroxide solution, mixing evenly and filtering to obtain slurry, sending the slurry into an oven, setting 95°C for 60 minutes, and obtaining bamboo fiber; Add bamboo fiber mixed with tris(hydroxymethyl)aminomethane solution into a beaker, the mass ratio of bamboo fiber to tris(hydroxymethyl)aminomethane is 1:0.5, react at room temperature for 10 minutes, stir continuously during the reaction, and put into an oven after the reaction is completed, set at 90°C for 3 hours, to obtain the first additive; S3, prepare the second additive for standby use; The second additive is prepared by the following method: wheat grains are selected as raw materials, the wheat grains are ground and sieved to obtain wheat flour, the wheat flour is placed in a copper precipitation solution, the mass ratio of wheat flour to copper precipitation solution is 1:1.4, after mixing and reacting for 20 minutes, the wheat flour and the copper precipitation solution are separated by filtering, and the flour is spread out and placed in a ventilated place to dry, so as to obtain the second additive; S4, mixing the first additive obtained in step S2 with the second additive obtained in step S3 to obtain a modified additive; The modified additive is prepared by the following method: the first additive and the second additive are fed into a mixer for mixing, the mass ratio of the first additive to the second additive is 1:1.8, the mixer is set to stir at a medium-low speed for 8 minutes, polydimethylsiloxane accounting for 15% of the mass of the first additive is added during the mixing process, and after the mixing is completed, it is placed in an oven at 70° C. for 3 hours, and then taken out, ground and sieved to obtain the modified additive; The screening particle size of modified additives is ≤65μm, and the screening particle size of preliminary carbonized materials is ≤80μm; S5, mixing the preliminary carbonized material obtained in step S1 with the modified additive obtained in step S4 to obtain a precursor; S6, cross-linking the precursor obtained in step S5 with carbohydrates, wherein the carbohydrates are corn starch, and obtaining an intermediate after sintering and annealing, and the intermediate is subjected to curing and carbonization treatment to prepare a fossil-based hard carbon material; The cross-linking reaction temperature of the precursor and carbohydrate is 350°C, the reaction time is 12h, and the sintering annealing temperature is 500°C; The temperature of the curing treatment was 1100°C, the heating rate was 30°C / min, and the temperature was kept for 2h. The temperature of the carbonization treatment was 1600°C, the heating rate was 12°C / min, and the temperature was kept for 6h. This embodiment also provides a fossil-based hard carbon material, which is prepared by the method for preparing a fossil-based hard carbon material.

[0026] Comparative Example 1: The difference between this comparative example and Example 1 is that: This embodiment does not contain the first additive, and other method steps are the same as those in Embodiment 1.

[0027] Comparative Example 2: The difference between this comparative example and Example 1 is that: This embodiment does not contain the second additive, and other method steps are the same as those in Embodiment 1.

[0028] Comparative Example 3: The difference between this comparative example and Example 1 is that: In this embodiment, polydimethylsiloxane is not added when preparing the modified additive, and other method steps are the same as in Example 1.

[0029] Comparative Example 4: The difference between this comparative example and Example 1 is that: In this embodiment, the mixture is not dried when preparing the second additive, and other method steps are the same as in Embodiment 1.

[0030] Performance test: The relevant properties of the hard carbon material samples provided in Examples 1 to 3 and Comparative Examples 1 to 4 were tested respectively. In the performance test, the hard carbon materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were processed into electrode sheets by the same method, and assembled in the order of negative electrode shell, sodium sheet, diaphragm, negative electrode sheet, gasket, spring sheet, and positive electrode shell. The electrochemical performance of the button battery test was tested, and the charge and discharge voltage range was 0V to 2.0V, and the rate was 0.1C; The test results are recorded in the following table:

[0031] By comparing and analyzing the relevant data in the table, it can be seen that the hard carbon material prepared by the present invention not only has good coulombic efficiency, but also has excellent charge and discharge performance. This shows that the fossil-based hard carbon material and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0032] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0033] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

[0034] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.

Claims

1. A method for preparing a fossil-based hard carbon material, characterized in that: The following steps are involved: S1: Select fossil-based raw materials, perform preliminary carbonization treatment on the raw materials, and obtain preliminary carbonized materials after grinding and sieving; S2: preparing the first additive for standby use; S3: preparing the second additive for standby use; S4: mixing the first additive obtained in step S2 with the second additive obtained in step S3 to obtain a modified additive; S5: mixing the preliminary carbonized material obtained in step S1 with the modified additive obtained in step S4 to obtain a precursor; S6: cross-linking the precursor obtained in step S5 with carbohydrates, obtaining an intermediate after sintering and annealing, and preparing a fossil-based hard carbon material by subjecting the intermediate to curing and carbonization treatment.

2. The method for preparing a fossil-based hard carbon material according to claim 1, characterized in that: The fossil-based raw material is selected from any one of anthracite, bituminous coal and lignite.

3. The method for preparing a fossil-based hard carbon material according to claim 1, characterized in that: The first additive is prepared by the following method: selecting recycled bamboo chopsticks as raw materials, and starting the preparation operation after the recycled bamboo chopsticks are washed and dried, sending the recycled bamboo chopsticks into a crusher for 4 to 6 minutes to obtain bamboo chips, mixing the bamboo chips with potassium hydroxide solution and adding them into a beaker, wherein the mass ratio of the bamboo chips to the potassium hydroxide solution is 1:3, heating to 80 to 90°C after mixing, keeping the temperature for reaction for 4 to 6 hours, cooling to room temperature after the reaction is completed, adding deionized water accounting for 50 to 60% of the mass of the potassium hydroxide solution, mixing evenly and filtering to obtain slurry, sending the slurry into an oven, setting 85 to 95°C, and the time is 50 to 60 minutes to obtain bamboo fiber.

4. The method for preparing a fossil-based hard carbon material according to claim 3, characterized in that: Add bamboo fiber mixed with tris(hydroxymethyl)aminomethane solution into a beaker, wherein the mass ratio of bamboo fiber to tris(hydroxymethyl)aminomethane is 1:0.5, and react at room temperature for 5 to 10 minutes with continuous stirring during the reaction. After the reaction, place the mixture into an oven at 80 to 90° C. for 2 to 3 hours to obtain a first additive.

5. The method for preparing a fossil-based hard carbon material according to claim 1, characterized in that: The second additive is prepared by the following method: wheat grains are selected as raw materials, and wheat flour is obtained after the wheat grains are ground and sifted, and the wheat flour is placed in a copper precipitation solution, and the mass ratio of the wheat flour to the copper precipitation solution is 1: (1.2-1.4). After mixing and reacting for 10-20 minutes, the wheat flour and the copper precipitation solution are separated by filtering, and the flour is spread out and placed in a ventilated place to dry, so as to obtain the second additive.

6. The method for preparing a fossil-based hard carbon material according to claim 1, characterized in that: The modified additive is prepared by the following method: the first additive and the second additive are fed into a mixer for mixing, the mass ratio of the first additive to the second additive is 1: (1.6-1.8), the mixer is set to stir at a medium-low speed for 5-8 minutes, polydimethylsiloxane accounting for 10-15% of the mass of the first additive is added during the mixing process, and after the mixing is completed, it is placed in an oven at 60-70° C. for 2-3 hours, and then taken out, ground and sieved to obtain the modified additive.

7. The method for preparing a fossil-based hard carbon material according to claim 1, characterized in that: The sieved particle size of the modified additive is ≤65 μm, the sieved particle size of the preliminary carbonized material is ≤80 μm, and the carbohydrate in step S6 is corn starch.

8. The method for preparing a fossil-based hard carbon material according to claim 1, characterized in that: The cross-linking reaction temperature of the precursor and the carbohydrate is 250-350°C, the reaction time is 5-12h, and the sintering annealing temperature is 400-500°C.

9. The method for preparing a fossil-based hard carbon material according to claim 1, characterized in that: The temperature of the curing treatment is 800-1100°C, the heating rate is 20-30°C / min, and the heat preservation is 1-2h. The temperature of the carbonization treatment is 1300-1600°C, the heating rate is 8-12°C / min, and the heat preservation is 3-6h.

10. A fossil-based hard carbon material, characterized in that: The hard carbon material is prepared by the method for preparing the fossil-based hard carbon material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Improved secondary li ion battery and li capacitor electrode compositions

    CA3038800A1

  • Preparation method of bamboo hard charcoal material and bamboo hard charcoal material

    CN117602610A

  • Carbon-based composite structure material as well as preparation method and application thereof

    CN117985689A

  • Coal-based hard carbon as well as preparation method and application thereof

    CN118004996A

  • Composite hard carbon material and preparation method and application thereof

    CN118495513A

Cited By

  • Self-supporting membrane negative electrode material, preparation method thereof and sodium ion battery

    CN119812204A

  • Preparation method of silicon-carbon negative electrode material

    CN120398065A